PENGARUH SISTEM INFORMASI AKUNTANSI PENGGAJIAN TERHADAP PRODUKTIVITAS KARYAWAN PADA PT DYNACAST INDONESIA - Effendi, Syahril (Measurement : Jurnal Akuntansi, 2014)
This study aimed to examine the effect of the application of payroll accounting information system on the productivity of employees at PT. Dynacast Indonesia. In this study, researchers linked the payroll accounting information system that is used and owned company with employee productivity.Hypotheses obtained in this study produces components perpengaruh payroll accounting information system positively on the productivity of the employee's performance which in processing statistical data is calculated with the use of the program SPSS version 16.Keywords: Accounting Information Systems, Payroll, Employee Productivity.